2018
DOI: 10.1080/15325024.2018.1428484
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Dysmorphia Research Neglects DSM-5 Diagnostic Criteria

Abstract: This systematic review aimed to collect, evaluate, and synthesize the research on muscle dysmorphia (MD) post official recognition as a specifier for body dysmorphic disorder (BDD) in the DSM-5, and provide recommendations for future research. Literature searches were conducted in four databases to see if inclusion criteria were met. Results revealed 33 studies meeting inclusion criteria, none of which utilized DSM-5 criteria for MD and/or acknowledged the criterion in their research. Few studies acknowledged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…Although the phenomenon is poorly understood, initial evidence suggests that concerns with physical appearance may represent a continuum from healthy behaviours to psychopathological manifestations related to various forms of anxiety. On this spectrum severe obsessive-compulsive behaviours such as Body Dysmorphic Disorder (BDD) [16, 17] and Muscle Dysmorphia (MD) [18] could be identified. Such disorders could act as precursors or be symptomatic of other clinical conditions, such as eating disorders, mood disorders and addictive behaviours [19, 20, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the phenomenon is poorly understood, initial evidence suggests that concerns with physical appearance may represent a continuum from healthy behaviours to psychopathological manifestations related to various forms of anxiety. On this spectrum severe obsessive-compulsive behaviours such as Body Dysmorphic Disorder (BDD) [16, 17] and Muscle Dysmorphia (MD) [18] could be identified. Such disorders could act as precursors or be symptomatic of other clinical conditions, such as eating disorders, mood disorders and addictive behaviours [19, 20, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…MD is currently classified as a subtype of BDD in the DSM 5 [ 1 ]; however, debate continues regarding its nosology [ 10 12 ]. This debate is due largely to most of the research on MD being conducted with non-clinical undergraduate students with self-report measures [ 13 ]. The disproportionate focus on undergraduate samples and reliance of self-report measures leaves gaps in the literature, particularly given that self-report measures alone cannot confer clinical diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Such obsessions with the body can lead to serious clinical disorders, leading to loss of employment, loss of family and friends, or depression, suicide and even death, as well as kidney failure, heart diseases, and damaged self-esteem. [14][15][16] Research has shown that eating disorders and MD show similarities in most ways. 7 Obsession with having more muscle mass in people with MD has been found to cause serious eating disorders at a psychopathological level.…”
Section: Introductionmentioning
confidence: 99%